PENGAKUAN, PENGUKURAN, PENYAJIAN DAN PENGUNGKAPAN DANA NON HALAL PADA LAPORAN KEUANGAN LEMBAGA AMIL ZAKAT - Ahmad Roziq; Widya Yanti (Universitas Jember, 2013)
In Islam economic instrument, there is optimaze of zakah that must be supported with riba disbandment so it is able to create society prosperity. The phenomena of non halal fund at LAZ also cause controversial in ulama society until now and there is not MUI fatwa yet that discuss about its non halal fund. This research purpose is to know and analyze the accounting treatment of Amil Zakah Institution in non halal fund and compare it with PSAK 109. Type of this research is qualitative research with descriptive analysis approach, and data collecting method that used is case study with take LAZ Yatim Mandiri, LAZ Rumah Zakat, and LAZ DD Surabaya as the research objects. Non halal treatment at these LAZ is include the confession, presentation, and expressing and still not appropriate with non halal fund rule at ED PSAK 109 and PSAK 109, whereas to non halal fund measurement have been appropriate with PSAK 109. So that, in the future, the three LAZ must be recognize non halal fund acceptance as non halal fund and it should provide separately from zakah fund, infaq fund, amil fund and wakaf fund. In addition, dana non halal fund source must only originate from bank interest and giro, that amount is not too large and distributed for Muslim public interest out from consumption and religious facility. Keywords : LAZ, Non-Halal Fund, Treatment Of Accounting, ED PSAK109 dan PSAK 109